Preparation And Characterisation Of Starch Propionate: Effect Of Ph, Nacl Salt Solutions And Application As Emulsion Stabiliser In Food - Hong, Lee Fen (2019)
Octenylsuccinylated starch (a modified starch) is the only commercially available emulsion sabiliser in food industry. Hence, it is timely to explore other modified starch as emulsion stabiliser. Starch propionate (SP) has been evaluated as resistant starch but not as emulsion stabiliser. However, its preparation was complicated involving multiple steps, long reaction time and use of toxic catalyst. The objective of the study was to prepare SP using a simple, one step process with environmentally friendly catalyst, followed by evaluation as emulsion stabiliser. SP with degree of substitution (DS) of 0.21-0.94 was successfully prepared using corn starch to propionic anhydride at mole ratios of 1:3, 1:4 and 1:6, with reaction time from 1 – 12 h. The propionylation was confirmed with FTIR and NMR. As DS increased, SP showed a decrease in crystallinity but an increase in hydrophobicity as reflected from X-ray diffraction and contact angle results, repectively. Oil-in-water emulsions prepared with starch propionate (DS 0.21-0.94) with viscosities between 993.3-5413.3 mPa.s were stable under centrifugation stress study. SP (DS 0.21) prepared with corn starch:propionic anhydride at mole ratio of 1:3 and reaction time of 1 h was chosen for further study. SP prepared in pH 3.5-11.5 or 0.5 M salt solutions showed increased pasting viscosity, swelling property and textural property, when compared to SP prepared in buffer pH 2.0; 1.0 M salt solution or 2.0 M salt solutions.